Exploring factors influencing domestic violence: a comprehensive study on intrafamily dynamics - Lanchimba, Cintya; Díaz-Sánchez, Juan Pablo; Velasco, Franklin (Frontiers in Psychiatry, 2023)
This study utilizes econometric analysis to investigate the relationship between household factors and violence within households. By examining variables such as mood, depression, health consciousness, social media usage, household chores, density, and religious affiliation, we aim to understand the dynamics that contribute to domestic violence. The results reveal significant associations between these variables and violence levels. Positive mood is found to decrease violence, while depression shows a positive relationship with violence, indicating higher conflict levels. Health consciousness is associated with reduced violence, and social media usage is found to have a mitigating effect. Decreased time spent on household chores correlates with lower violence levels. Density within households is positively linked to violence. Religious affiliation displays varying effects depending on household position and gender. These findings provide valuable insights for policymakers and practitioners working towards violence prevention and intervention strategies.Standard errors in brackets * p < 0.1, ** p < 0.05, *** p < 0.01